Coronary artery stenosis associated with right ventricular dysfunction in acute pulmonary embolism: A case-control study - Yuejiao Ma; Jieling Ma; Dan Lu; Yinjian Yang; Chao Liu; Liting Wang; Xijie Zhu; Xianmei Li; Chunyan Cheng; Sijin Zhang; Jiayong Qiu; Jinghui Li; et al. (Chinese Medical Journal)
Abstract. Background:. The potential impact of pre-existing coronary artery stenosis (CAS) on right ventricular (RV) function during acute pulmonary embolism (PE) episodes remains underexplored. This study aimed to investigate the association between pre-existing CAS and RV dysfunction in patients with acute PE. Methods:. In this multicenter, case-control study, 89 cases and 176 controls matched for age were enrolled at three study centers (Peking Union Medical College Hospital, Fuwai Hospital, and the Second Affiliated Hospital of Harbin Medical University) from January 2016 to December 2020. The cases were patients with acute PE with CAS, and the controls were patients with acute PE without CAS. Coronary artery assessment was performed using coronary computed tomographic angiography. CAS was defined as ≥50% stenosis of the lumen diameter in any coronary vessel >2.0 mm in diameter. Conditional logistic regression analysis was used to evaluate the association between CAS and RV dysfunction. Results:. The percentages of RV dysfunction (19.1% [17/89] vs. 44.6% [78/176], P <0.001) and elevated systolic pulmonary artery pressure (sPAP) (19.3% [17/89] vs. 39.5% [68/176], P = 0.001) were significantly lower in the case group than those in the control group. In the multivariable logistic regression model, CAS was independently and negatively associated with RV dysfunction (adjusted odds ratio [OR]: 0.367; 95% confidence interval [CI]: 0.185–0.728; P = 0.004), and elevated sPAP (OR: 0.490; 95% CI: 0.252–0.980; P = 0.035), respectively. Conclusions:. Pre-existing CAS was significantly and negatively associated with RV dysfunction and elevated sPAP in patients with acute PE. This finding provides new insights into RV dysfunction in patients with acute PE with pre-existing CAS.